Recent achievements in prenatal genetic diagnosis of small supernumerary marker chromosomes - M. A. Omarov; A. R. Mulyukov; I. A. Burmistrov; E. I. Akhmadishin; M. S. Lapteva; A. N. Nizamutdinova; K. Z. Nurieva; R. A. Iagudina; M. R. Kurbanadamov (Сибирский научный медицинский журнал, 2024)
Small supernumerary marker chromosomes (sSMCs) are structurally abnormal chromosomes that cannot be clearly identified or characterized by traditional karyotyping. They can appear in a variety of forms, including rings, centric fragments, and other structural abnormalities, and are often detected during prenatal diagnosis. sSMCs occur in approximately 0.075 % of unselected prenatal cases and can be associated with a wide range of phenotypic presentations, from normal development to severe congenital malformations and syndromes. Understanding and interpreting the clinical significance of sSMCs remains challenging in genetic counseling due to their high heterogeneity and potential impact on fetal phenotype. Advances in the field of molecular cytogenetics, including techniques such as fluorescence in situ hybridization (FISH), as well as microarray comparative genomic hybridization (aCGH) and next-generation sequencing (NGS), have significantly improved the ability to accurately characterize sSMCs. These methods can determine their origin, size and genetic content, which is critical for risk assessment and decision-making during pregnancy. Thus, modern molecular cytogenetics techniques play a key role in the identification and characterization of sSMC, allowing for more accurate genetic counseling and helping to make informed pregnancy decisions. However, despite technological advances, sSMCs continue to pose a challenge for prenatal diagnosis due to their complexity and potential impact on fetal development. In this article, we aim to provide a general overview of sSMCs and of their impact on prenatal diagnosis, as well as consider the clinical significance and potential impact of sSMCs on pregnancy outcome.